Determinasi Pengungkapan Syariah terhadap Standar AAOIFI : Studi terhadap Daftar Efek Syariah di Indonesia - Ahmad Dzakiyuddin (Prodi Hukum Ekonomi Syariah Fakultas Agama Islam, Universitas Muhammadiyah Purwokerto, 2019)
The purpose of this study is to determine the impact of compliance with sharia principles, leverage ratio, revenue recognition ratio and islamic governance score on the disclosure level. Compliance with sharia principles is measured in accordance with the capital market and Financial Institution Supervisory Agency Regulations concerning Criteria for Issuance of List of Sharia Securities. The leverage ratio and revenue recognition ratio are determined using the criteria set by DSN-MUI and written on OJK regulations concerning Criteria and Issuance of List of Sharia Securities. Meanwhile the Islamic Governance Score is a proxy for the characteristics of the Sharia Supervisory Board (DPS). Level of disclosure measured by formulating a disclosure index based on Sharia Company Theory. The sample in this study was 343 Lists of Sharia Securities in Indonesia in 2018. The results of the study indicate that all independent variables are significant for the disclosure level.